Knowledge, attitude, and practice of intensive care nurses toward delirium: a multicenter cross-section study - Dai, Dabing; Tian, Yongming; Jing, Wenwen; Liu, Huan; Xu, Yu (Frontiers in Medicine, 2025)
BackgroundDelirium is a common and serious complication among patients in the Intensive Care Unit (ICU). Nurses have an essential role in dealing with delirium in critical illness. However, understanding of ICU nurses’ knowledge, attitude, and practice (KAP)on delirium is limited, and large-scale survey lacking.ObjectivesTo explore the status and related factors of KAP of delirium among critical care nurses in China.MethodsFrom February to May 2019, a cross-sectional survey was conducted among 3,199 intensive care nurses from 160 hospitals across China using a convenience sampling approach. An online questionnaire was designed and distributed to evaluate the KAP of nurses. Univariate and multivariate linear regression analyses were used to assess the factors that influenced ICU nurses’ KAP.ResultsA total of 3,199 valid questionnaires were collected. Overall, the scores of ICU nurses’ knowledge, attitude, and practice regarding delirium assessment were 38.00 (33.00, 44.00), 23.00 (19.00, 26.00), and 16.00 (12.00, 19.00), respectively. Among the respondents, the proportions of individuals providing positive responses regarding their knowledge, attitude, and practice scores were 48.59%, 58.27%, and 40.52%, respectively. The attitude scores of the nurses were significantly related to knowledge scores (p < 0.001). Moreover, the scores for nurses’ practice show a significant correlation with their knowledge scores (p < 0.001) and attitudes scores (p < 0.001). Multivariate linear regression analysis showed a higher level of education (P = 0.037), surgical ICU (P = 0.02), private hospital (P < 0.001), clinical position (P = 0.007), shorter working hours (P < 0.001), primary professional title (P < 0.001), and previous experience in delirium nursing (P < 0.001)and training (P < 0.001)were related to higher practice scores.ConclusionThe knowledge of delirium among ICU nurses is at a moderate level. While these nurses exhibit a positive attitude toward this issue, their actual practices tend to reflect a relatively negative approach. Managers and nursing researchers should develop and offer standardized training for critical care nurses to improve their KAP toward delirium in critically ill patients.